Utilization of Artificial Intelligence (AI) Applications and Critical Thinking Skills of FAI Students at Nusantara Islamic University - Pingki Ode; Aqsyal Wahyu Aditia; Wafa Yudhia Darma; Nur Ainiyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research shows that the use of artificial intelligence (AI) by students of the Faculty of Islamic Studies (FAI) at UNINUS has become an integral part of their academic activities. AI is widely used, from helping students understand material and organize assignments to quickly answering various academic questions. On the one hand, the presence of AI offers many benefits in supporting the learning process, such as facilitating access to information and accelerating the achievement of academic results. However, on the other hand, a serious challenge has emerged, namely the tendency for students to rely on instant solutions without a deep reflective process